Creative communities : art works in economic development - Rushton, Michael, 1959- (Brookings Institution Press, 2013)
"Examines the impacts of arts and cultural consumption and production on local economies. Topics include location choices of arts entrepreneurs; links between the arts and non-arts sectors; public policies to foster local arts; and the arts' effects on incomes in cities across the United States and the United Kingdom"--Vydavatelská anotace
"Sponsored by the National Endowment for the Arts, Office of Research and Analysis."--Tit.s.
Vychází z příspěvků prezentovaných na Brookings Institution symposium "The arts, new growth theory, and economic development", květen 2012
Keywords: umění -- ekonomické aspekty; umění a společnost -- ekonomické aspekty; regionální ekonomie; ekonomický růst; kulturní průmysl; art -- economic aspects; art and state -- economic aspects; regional economics; economic development; cultural industries; sborníky konferencí; proceedings of conferences